Pertanggungjawaban Pidana Tenaga Kesehatan Terhadap Malpraktik Dan Negligence Dalam Tindakan Khitan (Sirkumsisi) - Sibarani, Tamara Roully; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Errors of Practice (malpractice) occur or caused a malfunction that canbe less cautious, less careful, and less seriousness in the anamnesis, examination,diagnosis, therapy/treatment and follow-up, on the other side because it is lessskilled and lack of knowledge from the healthcare personnel concerned. The studytitled